ӘЖИНИЯЗ ҚОСЫҚЛАРЫНДА ЛИРИКАЛЫҚ КОНФЛИКТ ЖАРАТЫЎДА МЕТАФОРАНЫҢ ХЫЗМЕТИ - Досымбетова, А. (SCIENCE and SOCIETY, 2025)
The article studies the lyrical works of the classic of Karakalpak literature Azhiniyaz Kosybayuly. The role of lyrical conflict in creating the image of the lyrical hero in the poet’s poems is analyzed. It is investigated how through the lyrical conflict the views of the lyrical hero on the era in which he lived are conveyed. Special attention is paid to the use of metaphors in the creation of lyrical conflict. The artistic function of metaphors in the poems and their significance in the formation of lyrical conflict are studied.